2022
DOI: 10.4103/idoj.idoj_257_21
|View full text |Cite
|
Sign up to set email alerts
|

Bowen's Disease

Abstract: Bowen's disease (BD) is an in-situ squamous cell carcinoma of epidermis. The etiology of BD is multifactorial with high incidence among Caucasians. BD is common in photo-exposed areas of skin, but other sites can also be involved. Lesions are usually solitary. The morphology of BD differs based on age of the lesion, site of origin, and the degree of keratinization. BD is considered as the “lull before the storm,” which precedes an overt squamous cell carcinoma. Histopathology is the gold standard diagnostic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 91 publications
(144 reference statements)
0
77
0
2
Order By: Relevance
“…Bowen's disease, which turns out to be a precancerous condition of squamous cell carcinoma, is a rare disease but one of the major types of skin cancer. [ 21 ] When asked if Bowen's disease was hereditary, 21–30 years old said they were hereditary (41.88%) [ Figure 5 ]. Bowen's disease is a noninvasive precancerous condition, also known as intraepithelial squamous cell carcinoma, but our findings show that approximately 44.02% of the 21–30-year-old age group is an invasive form which was contraindicated [ Figure 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bowen's disease, which turns out to be a precancerous condition of squamous cell carcinoma, is a rare disease but one of the major types of skin cancer. [ 21 ] When asked if Bowen's disease was hereditary, 21–30 years old said they were hereditary (41.88%) [ Figure 5 ]. Bowen's disease is a noninvasive precancerous condition, also known as intraepithelial squamous cell carcinoma, but our findings show that approximately 44.02% of the 21–30-year-old age group is an invasive form which was contraindicated [ Figure 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…При этом запускаются такие механизмы, как инактивация генов, подавляющих р53, которые, в свою очередь, вызывают агрессивное развитие злокачественных новообразований кожи и в первую очередь болезни Боуэна [12]. Некоторые вторичные причины возникновения (различные виды повреждения и воспалительные процессы в коже) могут спровоцировать болезнь Боуэна, особенно у пожилых людей [13].…”
Section: этиологические факторы возникновения болезни боуэнаunclassified
“…Что касается современных методов лечения болезни Боуэна, то указать конкретный наиболее эффективный метод терапии, к сожалению, нельзя. Согласно зарубежным клиническ им рекомендациям, можно использовать несколько различных методов лечения [10,13]. Специфическое лечение в каждом конкретном случае зависит от множества факторов.…”
Section: современные аспекты диагностики и лечения болезни боуэнаunclassified
“…Patients with BD have an increased risk of developing invasive cSCC 3 . Approximately 10%–20% of patients with BD may develop multiple lesions 4 . Although recent studies have revealed the genomic landscape of BD, 5–7 few studies have evaluated the genomics of multiple BD.…”
Section: Introductionmentioning
confidence: 99%
“…3 Approximately 10%-20% of patients with BD may develop multiple lesions. 4 Although recent studies have revealed the genomic landscape of BD, 5-7 few studies have evaluated the genomics of multiple BD. A case of multiple BD with cancer-predisposing Li-Fraumeni syndrome caused by a germline TP53 mutation 8 and a case series of multiple BD with different TP53 somatic mutations have been reported, 9…”
mentioning
confidence: 99%